Swarm based mean-variance mapping optimization (MVMOs) for economic dispatch problem with valve-Point effects - Khoa, T.H. (IEEE Computer Society, 2014)
Mean-variance mapping optimization (MVMO) is a novel population-based meta-heuristic technique which has been successfully applied for different power system optimization problems. The special feature of MVMO is the mapping function applied for the mutation based on the mean and variance of n-best population. Recently, the modified version of MVMO has been developed to get more powerful, named as Swarm based Mean-variance mapping optimization (MVMOs). This paper proposes MVMOs as a new approach for solving the economic dispatch problem considering valve-point effects. To demonstrate the performance of the proposed method, the proposed MVMOs has been tested on two systems including 3 and 13 thermal generating units with valve-point effects and the obtained results from MVMOs have been compared to those from other existing methods in the literature. It is indicated that the proposed MVMOs is efficient for solving the economic dispatch with valve-point effects. Â© 2014 IEEE.